Functional and histopathological changes induced by intraparenchymal injection of kainic acid in the rat cervical spinal cord - Nishida, Fabián (2015)
Kainic acid (KA) is an analog of the neurotransmitter glutamate and is widely used as an excitotoxic agent to lesion spinal cord networks, thus, providing an interesting model to learn basic mechanisms of spinal cord injury. The present work was aimed to evaluate motor and sensory performance of rats and analyze morphometric parameters of spinal cord neurons after KA injection. Animals were injected either with 0.75, 1 or 1.25 mM of KA at the C5 segment of the cervical spinal cord. Motor and sensory performance of the rats were evaluate at day 0 (before injection) and at days 1, 2, 3 and 7 post-injection (pi) and compared with those of saline-treated and non-operated animals. Animals were sacrificed at each time point for morphometric and histopathological analysis and compared among groups. All KAtreated animals showed a significant impairment at the motor and sensory tests for the ipsilateral forelimb in a concentration-dependent manner in comparison to saline-treated and non-operated animals. Neuronal cell count showed a significant loss of neurons at C4, C5 and C6 cervical segments when compared with those of saline-treated and non-operated animals. The contralateral side of the cervical segments in KA-treated rats remained unchanged. Some improvement at the motor and sensory tests was observed in animals injected with 0.75 and 1 mM KA. Moreover, a mild increase in the neuronal count of the damaged segments was also recorded. The improvement recorded in the motor and sensory tests by day 7 pi may be a consequence of a neuron repairing mechanism triggered soon after the KA excitotoxic effect.